2022
DOI: 10.1109/access.2022.3175210
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Force Measurement and Mapping Using Pressure-Sensitive Film and Image Processing for Active and Passive Aligners on Orthodontic Attachments

Abstract: The authors would like to express their gratitude to the technicians, especially Daniel Liam from WhiteSmileclear Laboratory Services, for their assistance and supporting staff from Universiti Kebangsaan Malaysia (UKM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The in vitro study by Zamani et al [ 50 ] reported a similar magnitude of the force in active aligners with ellipsoidal attachment generating an average mean force of 6.18 N and 6.34 N for rectangular attachment. Notwithstanding, the authors used both active and passive CAs.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The in vitro study by Zamani et al [ 50 ] reported a similar magnitude of the force in active aligners with ellipsoidal attachment generating an average mean force of 6.18 N and 6.34 N for rectangular attachment. Notwithstanding, the authors used both active and passive CAs.…”
Section: Discussionmentioning
confidence: 80%
“…In our work, pressure mapping was achieved via a non-destructive technique [ 49 ]. The method for force measurement was adopted from Zamani et al [ 50 ]. The orthodontic force generated by the CA was measured using the pressure-sensitive film (Fuji Prescale Film, Fujifilm Corporation, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 2 and 3 present the network meta-findings' analysis. Out of the 16 studies that we selected for the systematic review and subsequent meta-analysis, 1 was a comparative clinical trial [24], 2 were prospective studies [22,29], and the rest were in vitro studies that investigated different aligner materials [10,11,13,14,23,[25][26][27][28][30][31][32]. In the clinical trial by Ercoli et al [24], the study compared the Nuvola ® and Fantasy ® systems, looked at their material characteristics, and identified when to employ aligners.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Apart from this, the overall quality of the available evidence using the GRADE Pro software [GRADEpro GDT: GRADEpro Guideline Development Tool. McMaster University and Evidence Prime, 2022] was judged to be moderate for the in vitro studies and the prospective clinical studies [10,11,13,14,22,23,[25][26][27][28][29][30][31][32] that analyzed the effects of aligner materials and attachments on orthodontic activity, and high for the one clinical trial [24] that was included in the review.…”
Section: Risk Of Bias Assessment Within the Studymentioning
confidence: 99%